MicroRNA-138 controls hippocampal interneuron function and short-term memory in mice - Daswani, Reetu Ramesh; Gilardi, Carlotta; Soutschek, Michael; Nanda, Prakruti; Weiss, Kerstin; Bicker, Silvia; Fiore, Roberto; Dieterich, Christoph; Germain, Pierre-Luc; Winterer, Jochen; Schratt, Gerhard (eLife, 2022)
The proper development and function of neuronal circuits rely on a tightly regulated balance between excitatory and inhibitory (E/I) synaptic transmission, and disrupting this balance can cause neurodevelopmental disorders, for example, schizophrenia. MicroRNA-dependent gene regulation in pyramidal neurons is important for excitatory synaptic function and cognition, but its role in inhibitory interneurons is poorly understood. Here, we identify miR138-5p as a regulator of short-term memory and inhibitory synaptic transmission in the mouse hippocampus. Sponge-mediated miR138-5p inactivation specifically in mouse parvalbumin (PV)-expressing interneurons impairs spatial recognition memory and enhances GABAergic synaptic input onto pyramidal neurons. Cellular and behavioral phenotypes associated with miR138-5p inactivation are paralleled by an upregulation of the schizophrenia (SCZ)-associated Erbb4, which we validated as a direct miR138-5p target gene. Our findings suggest that miR138-5p is a critical regulator of PV interneuron function in mice, with implications for cognition and SCZ. More generally, they provide evidence that microRNAs orchestrate neural circuit development by fine-tuning both excitatory and inhibitory synaptic transmission.
Version of record published: March 29, 2022 (version 2)
Mit zusätzlichen Informationen: Brief zur Entscheidung und Antwort der Autoren
Gesehen am 23.06.2022